Synergistic antileukemic effects of hydroxyurea and SRJ23 in T-cell acute lymphoblastic leukemia - Marashdeh, Laith; Stanslas, Johnson; Karuppiah, Thilakavathy; Khalid, Bahariah (Springer Science and Business Media, 2025)
Background T-cell acute lymphoblastic leukemia (T-ALL) is a highly aggressive blood cancer associated with high relapse rates, affecting about 15% of pediatric and 25% of ALL cases. Initial management typically involves hydroxyurea (HU) to reduce elevated white blood cell counts before intensive chemotherapy. However, despite this approach, recurrence remains a substantial challenge, even with stem cell transplants. A promising therapeutic strategy for T-ALL might involve combining HU with an additional compound that can enhance cancer cell inhibition. SRJ23, a semi-synthetic andrographolide derivative, is a potential candidate due to its unique mechanism of inhibiting the GDP-GTP exchange, targeting the oncogenic K-Ras mutation pathway implicated in T-ALL progression. This study investigates the potential of HU and SRJ23 as a combined treatment to enhance apoptotic induction in T-ALL cells.